Oestrogen receptor polymorphisms are an associated risk factor for mild cognitive impairment and Alzheimer disease in women APOE ɛ4 carriers: a case–control study. Issue 9 (18th September 2013) - Fernández-Martínez, Manuel; Elcoroaristizabal Martín, Xabier; Blanco Martín, Elisa; Galdos Alcelay, Luis; Ugarriza Serrano, Iratxe; Gómez Busto, Fernando; Álvarez-Álvarez, Maite; Molano Salazar, Ana; Bereincua Gandarias, Rocio; Inglés Borda, Sandra; Uterga Valiente, Juan María; Indakoetxea Juanbeltz, Begoña; et al.
Abstract : Objectives: Examine the role of single nucleotide polymorphisms (SNPs) in the oestrogen receptor (ER) genes: rs9340799, rs2234693, rs2228480 (in the ESR1 gene) and rs4986938 (in the ESR2 gene) as a risk factor for amnesic mild cognitive impairment (MCIa) and Alzheimer's disease (AD) and its possible association with the apolipoprotein E ( APOE) gene. Design: We have investigated the independent and combined association of different alleles of the oestrogen receptor genes and APOE*ɛ4 allele with cognitive impairment using a case–control design. Setting: Participants were prospectively recruited from the neurology departments of several Basque Country hospitals. Participants: This study comprised 816 Caucasian participants who were aged 50 years and older: 204 MCIa, 350 sporadic patients with AD and 262 healthy controls. Primary and secondary outcome measures: Clinical criteria and neuropsychological tests were used to establish the diagnostic groups (MCIa, AD and healthy controls). A dichotomous variable was used for each allele and genotype and the association with MCIa and AD was established using Logistic Regression Models. Results: Neither alleles nor genotypes of SNPs rs9340799, rs2234693, rs2228480 and rs4986938 of oestrogen receptor genes ( ESR1 and ESR2 ) are independently associated with the risk of MCIa or AD. However, the genetic profile created with the combination of the less represented alleles of these SNPs (expressed as XPAA) was associated with an increased risk for MCIa (OR=3.30, 95% CI 1.28 to 8.54, p=0.014) and AD (OR=5.16, 95% CI 2.19 to 12.14, p<0.001) in women APOE*ɛ4 allele carriers. Conclusions: The less represented alleles of SNPs studied are associated with MCIa and AD in APOE*E4 carriers. In particular, the genetic profile created with the less represented alleles of ESR1 and ESR2 SNPs are associated with an increased risk for MCIa and AD in women APOEɛ4 allele carriers.